May You Live in Interesting Times - Butler, Christopher (Hydro Nepal: Journal of Water, Energy and Environment, 2014)
Not Available. DOI: http://dx.doi.org/10.3126/hn.v15i0.11286 HYDRO Nepal Journal Journal of Water, Energy and Environment Volume: 15, 2014, July Page: 21-22